Analisis Pengaruh Penerapan Sistem Manajemen ERP Dalam Meningkatkan Kinerja Manajemen Rantai Pasok Pada PT Golden Visalux - Rizni Aulia Qadri; Immanuel Zai; Edward Cornelyanto; Jacelyn Christina Yeo; Febriyanti Febriyanti; Rina Rina; Tomi Vincent; Anisa Yessika Nababan (Public Service and Governance Journal, 2023)
When conducting business activities, a company definitely needs a plan or strategy that is clearly structured, and with the aim of managing the company's resources effectively and efficiently. One of the companies implementing a supply chain management system based on an Enterprise Resource Planning (ERP) system is Visalux. This article was written with the aim of analyzing the influence of Supply Chain Management & ERP Systems in improving the performance of Visalux companies. The research method used in this article is a qualitative descriptive method.